Mechanical properties of roller compacted concrete pavement containing coal waste and limestone powder as partial replacements of cement. (15th May 2016) - Hesami, Saeid; Modarres, Amir; Soltaninejad, Mostafa; Madani, Hesam
Graphical abstract: Highlights: 5–20% of cement was substituted with coal waste (CWP) and its ash (CWA). Mixes containing up to 5% CWP behaved similar to control mix. The combination of 7% limestone and CWA enhanced the mix properties. Relationships obtained as f t = 0.5 f c ′, f r = 0.9 f c ′ and E = 5600 f c ′, respectively. Abstract: This study investigates the effects of coal waste powder (CWP), coal waste ash (CWA), and limestone powder (LS) on the mechanical properties of roller compacted concrete pavement (RCCP). The mixtures were produced by partial replacement of cement with the supplementary cementitious materials at different incorporation levels of 5, 10 and 20%. The compressive strength, splitting tensile strength, flexural strength, and modulus of elasticity of RCCP mixtures were determined from 7 days up to 90 days. The results showed that the use of CWP and CWA increased the water/cementitious materials ratios. It is noteworthy that the RCCP mixtures containing 5% CWP or CWA showed equivalent performance to the control RCCP mixture. However, any further increase up to 20% substitution of cement with the supplementary cementitious materials decreased the strength values and elastic modulus of the mixtures at all ages. The combination of LS and CWA led to higher mechanical properties, especially at ages of 28 and 90 days. The relationships between the splitting tensile strength (ft ), flexural strength (fr ), modulus of elasticity (E) and compressive strength were obtained as f t = 0.5 f c ′, f r = 0.9 f c ′ and E = 5600 f c ′, respectively.